PENGARUH KEMAMPUAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL SANTIKA BENGKULU - Bagusta, Fitroandi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to determine the effect of work ability and work discipline on the performance of Santika Hotel Employees Bengkulu City. Respondents of this study were employees of Santika Hotel Bengkulu City totaling 70 employees. The sampling technique used in this study was total sampling. Data analysis techniques using multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of this study indicate that employee performance is influenced by work ability and work discipline. Furthermore, work ability and work discipline simultaneously or together have a significant effect on the performance of employees of Hotel santika Bengkulu City with a probability value (sig) of 0.000 <0.05. As well as work ability and work discipline partially or individually affect the performance of Santika Hotel employees in Bengkulu City with a probability value (sig) of each work ability variable with a probability value (sig) of 0.000 <0.050 has a significant effect on employee performance. And work discipline with a probability value (sig) of 0.000 <0.05 has a significant effect on employee performance.Keywords: Work Ability, Work Discipline and Employee Performance